GPs experience of caring for children with cancer receiving palliative care at home. (4th April 2011) - Neilson, S; Clifford, C; Kai, J; MacArthur, C; Greenfield, S
Abstract : Background: The study being undertaken builds on earlier work that found general practitioners (GPs) were at times uncertain of their role in paediatric palliative care and questioned whether their involvement had been beneficial to the child and family. The rarity of childhood cancer makes it difficult for GPs to develop or maintain palliative care knowledge and skills yet the GP is perceived by the family as the gatekeeper of care within the community. Aim: The study is examining GPs perception of their role in caring for an individual child with cancer receiving palliative care and comparing this with families' perceptions of their GP's roles. Methodology: The methodology incorporates tape-recorded semi-structured interviews, thematic framework analysis and Q methodology (QM) to capture the experiences of GPs who have cared for a child with cancer receiving palliative care as well as the perspectives of care experienced by the families. The semi-structured interview sample comprises 10 families (parents/guardians) whose child has been treated at a regional childhood cancer centre and their GPs. A further 40–60 GPs will be involved in the QM. Findings: Findings detailing GP experiences from the initial study along with the preliminary findings of the semi-structured interviews with parents and GPs will be presented. Papers' contribution: The results will identify and clarify GPs perceptions of their roles, and what families perceive their GPs role to be, enabling development of strategies to support GPs roles. It is anticipated that findings will inform the wider field of palliative care generally and the practice of both hospital and community paediatricians.